Pemahaman Perpajakan dan Religiusitas Memoderasi Penurunan Tarif Pajak dan Pelayanan Online pada Kepatuhan Wajib Pajak - Wirawan, I Made Dwi Sumba; Arygunartha, Gede Yohanes; Nida, Desak Rurik Pradnya Paramitha (E-Jurnal Akuntansi, 2021)
This study examines the effect of lowering tax rates and online services on taxpayer compliance and tests the ability to understand taxation and religiosity as moderating variables. The number of samples analyzed was 83 Micro, Small, and Medium Enterprises (MSMEs) which became partners of the Denpasar City Cooperative and UMKM Office. Determination of the sample in this study using probability sampling with simple random sampling method. The analysis technique used is multiple linear regression and Moderated Regression Analysis (MRA). The results of the analysis show that the reduction in tax rates and online services has a positive effect on taxpayer compliance. Understanding taxation and religiosity strengthens the reduction in tax rates on taxpayer compliance. However, understanding taxation and religiosity do not moderate the effect of online services on taxpayer compliance. Keywords: Reduction In Tax Rates; Online Services; Obedience; Understanding; Religiosity.